Teknik Penyelesaian Soal dengan Cara Means Ends Analysis (MEA) dalam Meningkatkan Penguasaan Hukum Hess pada Siswa SMA Negeri 2 Tondano - Tammu, Orpa; Waworuntu, Freetje (General Chemistry Journal, 2024)
The purpose of this study was to determine that the problem solving technique by Means Ends Analysis (MEA) can improve the mastery of Hess' Law of SMA Negeri 2 Tondano students. The type of research used is Quasi Experimental with a research design design that is one group pretest-posttest design. The sample in this study were all students of class XI IPA Room I which amounted to 20 people. In this study, the data collection instrument was a multiple choice test of 20 items in accordance with the material taught, namely Hess's Law. Data analysis in this study used validity and reliability tests. The results showed that the average student learning outcomes on the pretest were 44.25 while the average student learning outcomes on the posttest were 78.50. Based on the results of the N-gain Score test, the N-gain value obtained is 0.625349 and overall has quite effective criteria. In the N-gain Score, there are no students in the low category (0%), there are 14 students in the medium category (70%) and 6 students in the high category (30%). Based on the N-gain results that have been obtained, it can be concluded that the problem solving technique using Means Ends Analysis (MEA) can improve students' mastery of Hess's Law